Efficacy of cupping therapy on pain outcomes: an evidence-mapping study - Wang, Liaoyao; Cai, Ziling; Li, Xuanlin; Zhu, Aisong (Frontiers in Neurology, 2023)
Objective Cupping therapy is an ancient technique of healing used to treat a variety of ailments. An evidence-mapping study was conducted to summarize the existing evidence of cupping therapy for pain-related outcomes and indicate the effect and the quality of evidence to provide a comprehensive view of what is known. Methods PubMed, Cochrane Library, Embase, and Web of Science were searched to collect the meta-analyses investigating the association between cupping therapy and pain-related outcomes. The methodological quality was assessed by using the AMSTAR 2 tool. Significant outcomes (p < 0.05) were assessed using the GRADE system. The summary of evidence is presented by bubble plots and human evidence mapping. Results Fourteen meta-analyses covering five distinct pain-related conditions were identified and assessed for methodological quality using the AMSTAR 2, which categorized the quality as critically low (36%), low (50.0%), moderate (7%), and high (7%). In accordance with the GRADE system, no high-quality evidence was found that demonstrates the efficacy of cupping therapy for pain-related outcomes. Specifically, for neck pain, there were two moderate-quality, four low-quality, and two very low-quality evidence, while only one very low-quality evidence supports its efficacy in treating herpes zoster and one low-quality evidence for chronic back pain. Additionally, for low back pain, there were two moderate-quality, one low-quality, and four very low-quality evidence, and for knee osteoarthritis, three moderate-quality evidence suggest that cupping therapy may alleviate pain score. Conclusion The available evidence of very low-to-moderate quality suggests that cupping therapy is effective in managing chronic pain, knee osteoarthritis, low back pain, neck pain, chronic back pain, and herpes zoster. Moreover, it represents a promising, safe, and effective non-pharmacological therapy that warrants wider application and promotion. Systematic review registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021255879, identifier: CRD42021255879.